"We are Muslims and these diseases don't happen to us": A qualitative study of the views of young Somali men and women concerning HPV immunization. Issue 15 (3rd April 2019) - Pratt, Rebekah; Njau, Sharon W.; Ndagire, Channelle; Chaisson, Nicole; Toor, Sharondeep; Ahmed, Nimo; Mohamed, Saida; Dirks, Jay
Highlights: Young Somali American men and women's views on HPV vaccination address a gap in the literature. Catch-up vaccinations offer an opportunity to address HPV vaccine disparities in Somali youth. Authoritative approaches to vaccine engagement may lead to resistance in Somali immigrant youth. Somali American young adults value communication that builds trust and respect and affirms autonomy. Vaccine hesitancy may persist, or even increase, in second-generation Somali immigrants. Abstract: Background: Minnesota is home to the largest Somali immigrant population in the United States. Despite high rates of cervical cancer in this population, immunization rates for the human papillomavirus (HPV) are among the lowest in the nation. Targeting Somali young adults for catch-up vaccinations may be an important strategy for addressing these low rates. This study sought to understand the views of Somali young adults regarding HPV immunization. Methods: Four focus groups (N = 34; 21 women) were conducted at an urban clinic in Minnesota. Two groups were all female, one all male, and one mixed gender. Participants in each group discussed their views on immunization in general, and then their views on HPV immunization. Findings: Most participants had prior negative experiences with immunization and were skeptical concerning its value. In general, participants had low knowledge about HPV, though they expressed interest in knowing more. Views about HPV were influenced by culture, with risk perceived as low due to interpretations of religious beliefs and expectations around sexual behavior. Low levels of trust in doctors and other healthcare providers influenced participants' perceptions of the benefits of immunization. Participants also valued autonomy highly and resented having received required vaccinations without much choice, such as through their immigration experience or by school authorities. Participants suggested making more opportunities available for learning about HPV and how to prevent it, including via web-based platforms. Conclusion: An important opportunity exists to address low HPV immunization rates in the Somali American population by offering vaccination to young adults, who are interested in learning more about HPV. However, key barriers around HPV needs to be addressed in ways that respect the need for autonomy in this age group and that build trust with providers, which may mean avoiding authoritative approaches.